Forest Fires - Drohan, Michele Ingber 1832-1898.; Sir, 1820-1914 (New York PowerKids Press, 1999)
Discusses different kinds of forest fires, what causes them, where they occur, and how they can be prevented.
Issued also with marginal illustrations.
Keywords: Forest fires